The cathedral and the bazaar of e-repository development: encouraging community engagement with moving pictures and sound - Denis Wong; Kerry L. Shephard; Peter Phillips (Association for Learning Technology, 2008)
This paper offers an insight into the development, use and governance of e-repositories for learning and teaching, illustrated by Eric Raymond's bazaar and cathedral analogies and by a comparison of collection strategies that focus on content coverage or on the needs of users. It addresses in particular the processes that encourage and achieve community engagement. This insight is illustrated by one particular e-repository, the Education Media On-Line (EMOL) service. This paper draws analogies between the bazaar approach for open source software development and its possibilities for developing e-repositories for learning and teaching. It suggests in particular that the development, use and evaluation of online moving pictures and sound objects for learning and teaching can benefit greatly from the community engagement lessons provided by the development, use and evaluation of open source software. Such lessons can be underpinned by experience in the area of learning resource collections, where repositories have been classified as ‘collections-based' or ‘user-based'. Lessons from the open source movement may inform the development of e-repositories such as EMOL in the future.